Factors influencing the acceptance of internet banking among bank customers in Dungun, Terengganu / Nur Amirah Azman - Azman, Nur Amirah (2013)
Technology is affecting the life of every individual in this present age. Internet banking is also one of the technologies which are getting recognition around the world. The implementation of internet banking has become a necessity for every bank in ensuring that they are able to compete in the global market. This paper investigates the factors influencing the acceptance of internet banking among the consumers in a bank. With the perceived usefulness, perceived ease of use and aspects of security and privacy as independent variables, this paper examines how these factors influence the consumers to accept the internet banking services. This study used quota sampling technique in selecting the respondents and the respondent consists of the consumers in 10 different banks in Dungun. Correlation Coefficients were used to measure the overall picture of the factors influencing respondent’s acceptance. Using a sample of 248 respondents, evidence showed that perceived ease of use, perceived usefulness as well as the aspect of security and privacy are the factors contributing towards the acceptance. Multiple regression analysis was applied to look further into the relationship between the variables. Based on the findings, all the objectives of the study were answered. It is suggested that further study is conducted to investigate the criteria attracting the consumers to accept the internet banking services.